Use of plants as an alternative to synthetic agrochemicals in the cultivation of organics in Goiás (Research, Society and Development, 2021)
One of the main challenges of sustainable agriculture is the control of diseases, pests and invasive plants. In view of this, the current study aimed to conduct a literature review on the use of plant as an alternative to synthetic agrodefensivos in organics cultivation in Goiás. Natural pesticides such as the use of plants have been gradually supplied by synthetics, but recently, there is a growing interest in natural products for pest control. The organic food market in Goiás is still an introvert, however it has registered growth in production and demand in the last ten years. The rural worker has an interest in producing food without using pesticides. The methodology is a bibliographic review with a qualitative exploratory-descriptive design. It is concluded that the use of plants as an alternative to agrodefensive agents, is of paramount importance for farmers, since the plants are highly effective in combating pathogenesis and increase the producer's viability. Therefore, it is considered that the use of plants as an alternative to agrodefensives in the development of organic products in agriculture is an ecologically appropriate strategy.